2020
DOI: 10.1016/j.cytogfr.2020.05.003
|View full text |Cite
|
Sign up to set email alerts
|

The cytokine storm in COVID-19: An overview of the involvement of the chemokine/chemokine-receptor system

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
1,250
1
33

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,220 publications
(1,313 citation statements)
references
References 98 publications
29
1,250
1
33
Order By: Relevance
“…CXCL8 and its receptors contribute to pathogen elimination, through the transient activation of ERK, AKT, SRC and FAK leading to activation of neutrophils 26 . The expression of CXCL8, which is present in COVID-19 patients, is considered a potential prognostic factor in acute respiratory distress syndrome (ARDS) 29 and lung injury 30 .…”
Section: Discussionmentioning
confidence: 99%
“…CXCL8 and its receptors contribute to pathogen elimination, through the transient activation of ERK, AKT, SRC and FAK leading to activation of neutrophils 26 . The expression of CXCL8, which is present in COVID-19 patients, is considered a potential prognostic factor in acute respiratory distress syndrome (ARDS) 29 and lung injury 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Mc Gonagle et al illustrated that lung pathology seen in patients with COVID-19 shows marked alveolar and interstitial in ammation [17] It is currently believed that lung injury in COVID-19 not only associates with direct viral injury but also COVID-19 triggers immune response which leads to activation of immune cells and cytokine storm [18]. Cytokine storm extensively damages vascular endothelium and alveolar epithelium which increases vascular permeability leading to pulmonary edema and hyaline formation [19,20], similar to our ndings previous studies also reported aggravation of symptoms during 5-7 days after the disease onset [21], therefore it is important to control the in ammatory response and cytokine storm in this phase, however, by the systematic review, Nicola Veronese concluded that the routine use of corticosteroids in COVID-19 couldn't be encouraged, but methylprednisolone therapy could lower mortality rate in more severe forms of this condition, such as in severe respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
“…Mice model study also reveals the surge of chemokines in the lungs on SARS-CoV–2 infection(Shi-Hui-Sun et al 2020; Jason et al 2008). Elevation level was highest for inflammatory chemokines (macrophage inflammatory protein (MIP)-1α/CCL3, secreted (RANTES)/CCL-5, interferon-inducible protein (IP-10)/CXCL10 and monocyte chemotactic protein (MCP)-1/CCL2 upon SARS-Co-V infection and it may be true for other β-coronaviruses family viruses including SARS-CoV-2(Coperchini F, 2020; Zang et al 2020). We postulated that this lack of antiviral cytokine response against a background of intense chemokine upregulation could represent a mechanism of immune evasion by SARS-CoV-2; however, the genomic heterogeneity of S and N protein between SARS-CoV-2 and CARS-CoV-2 is essentially required to understand the immune escape mechanism.…”
Section: Discussionmentioning
confidence: 99%